The teachers' conflict in the peruvian press: The 2017 teachers' strike - Turpo-Gebera, Osbaldo; Pérez-Postigo, Gerber; Díaz-Zavala, Rocío (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
The press builds a set of media representations on the facts of reality. The teachers' strike of 2017 marked a substantial milestone in the construction of the news in the Peruvian press, due to the informative singularity and prevalent discourses. Based on the analysis of the informative treatment of the journalistic notes, the underlying media intentions are revealed to present the teachers' conflict, from the conjuncture or anecdote, avoiding its causes; on the contrary, they highlight the scandal or spectacularism of the news. In fact, the media opted for sensationalism, linking the teachers' crisis with violence, anarchy and urban chaos.